An Analysis on Students’ Ability in Writing Descriptive Text - Annisa Islami Fitri; Masrul Masrul; Putri Asilestari (Journal of English Language and Education, 2022)
English is the language used by almost everyone. In Indonesia, English is the first foreign language and a required subject in schools. Nowadays, not only a foreign language but also taught from secondary up to university. Learning English aims to master the four basic language skills of listening, speaking, reading, and writing. Students also begin to interact with others at the college level, they begin to learn to communicate in writing (Rianti 2016). In this section, the author focuses on writing. This research is a descriptive method. According to Nazir (1988:63) says that Descriptive method is a method of researching the status of a group of humans, an object, a set of conditions, a system of thought, or a class of events in the present. The purpose of this descriptive study was to create a description, picture, or painting in systematic, factual, and accurate information on the facts, properties, and relationships among the phenomena investigated. This research was conducted in SMA 2 Bangkinang Kota, located in Abdul Shaleh N0. 55, Bangkinang, Kampar, Riau. The total of students is 28. They consist of 12 males and 16 females. The main concern of this research was focused on the Analysis of students'' writing skills of descriptive text in the second grade of SMA 2 Bangkinang Kota. In this discussion of the result of students'' scores on writing ability of descriptive text. The result of the tests for the students was fair. Score the range showed that the mean score of test 1. The test of the students is categorized as good and fair. It means the level of excellence is no students or 0 % students. The level good is 8 or 32 % students. The fair level is 20 or 80 % students. From the discussion above the level of students in the test are fair. The student''s problems in writing skills of descriptive text are the student''s lack of vocabulary, which indicates the students did not bring a dictionary during when learning process and the students think that English vocabulary is hard to be learned. The students should always bring a dictionary when English learning. As already mentioned in the first chapter, the aim of this study are to describe students’ ability in writing a descriptive text focused on Content, Grammar, Vocabulary, Organization, and Mechanics in the Second Grade of SMA 2 Bangkinang Kota. The researcher would like to conclude that 28 students at XI IPA 3 in SMA 2 Bangkinang are fair in writing descriptive text. Based on the data presentation and the previous chapter, the researcher gets a conclusion of the research. The students'' writing skill in the descriptive text is fair. The result shows the mean score of the test is 69. It is classified that the students writing skills in the descriptive text of test are fair to level.